2011
DOI: 10.1111/j.1365-313x.2011.04841.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence recovery after photobleaching reveals high cycling dynamics of plasma membrane aquaporins in Arabidopsis roots under salt stress

Abstract: SUMMARYThe constitutive cycling of plant plasma membrane (PM) proteins is an essential component of their function and regulation under resting or stress conditions. Transgenic Arabidopsis plants that express GFP fusions with AtPIP1;2 and AtPIP2;1, two prototypic PM aquaporins, were used to develop a fluorescence recovery after photobleaching (FRAP) approach. This technique was used to discriminate between PM and endosomal pools of the aquaporin constructs, and to estimate their cycling between intracellular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
99
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 41 publications
11
99
1
Order By: Relevance
“…Salt stress is known to cause a dramatic increase in endocytic uptake (Leshem et al, 2007;Luu et al, 2012), resulting in the generation of intravesicular reactive oxygen species that act as second messengers in salt stress-elicited signaling pathways (Leshem et al, 2007;Golani et al, 2013). Salt stress is reported to elicit enhanced uptake and recycling of PM aquaporins in Arabidopsis root epidermis (Li et al, 2011;Luu et al, 2012). Such enhanced uptake is postulated to be partially due to the induction of a sterol-sensitive (lipid raft-dependent) pathway, which is not responsible for the uptake of aquaporins under control conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress is known to cause a dramatic increase in endocytic uptake (Leshem et al, 2007;Luu et al, 2012), resulting in the generation of intravesicular reactive oxygen species that act as second messengers in salt stress-elicited signaling pathways (Leshem et al, 2007;Golani et al, 2013). Salt stress is reported to elicit enhanced uptake and recycling of PM aquaporins in Arabidopsis root epidermis (Li et al, 2011;Luu et al, 2012). Such enhanced uptake is postulated to be partially due to the induction of a sterol-sensitive (lipid raft-dependent) pathway, which is not responsible for the uptake of aquaporins under control conditions.…”
Section: Discussionmentioning
confidence: 99%
“…6). A role for the endocytic pathway in DIM-enriched protein localization at specific sites in root cells and seedlings was accordingly demonstrated for aquaporin (Luu et al, 2012), dynaminrelated protein (Konopka et al, 2008), and flotillin (Li et al, 2012).…”
Section: Cryptogein Transiently Induces a Modification In Tobacco Celmentioning
confidence: 99%
“…The decline in the associated proteins does not, however, simply reflect degradation, but re-localisation to intracellular structures (Boursiac et al 2005). Studies of PIP1;2 and PIP2;1, in particular, have found that dispersion is heterogeneous and that salinity stress increases their internalisation and reduces their presence in the plasma membrane (Li et al 2011;Luu et al 2012). The subcellular trafficking is mediated by both clathrin and membrane raft pathways.…”
Section: Water and Transpirationmentioning
confidence: 99%